Dykha O.V., Dytynyuk V.O. An approximate solution to the wear-contact problem for a sliding bearing with a direct friction pair. - Диха, О. В.; Дитинюк, В. О. (Problems of Tribology, 2018)
An analysis of the schemes and tasks for slide bearings has shown that known approaches relate to the option: bearing wearing with a shaft that does not wear out. Known algorithms are difficult to implement in engineering practice. There is a need for common design schemes to get simple and convenient solutions for engineering practice. The system of calculation and experimental estimation of wear and reliability of sliding bearings is presented, which includes: methods of evaluation of working conditions without wear; method of determination of parameters of wear model; a method for determining the wear of bearing bearings under known parameters of wear pattern; method for assessing the reliability of the bearings of sliding. Calculations of wear of friction units are necessary at different stages of the existence of machines: at the design stage for the selection of optimal design parameters; at the manufacturing stage to assess the impact of technological factors on wear resistance; at the stage of operation to assess the service life and plan the amount of repair work. The proposed solving of the contact problem for the bearings of sliding, taking into account the wear with the finite simple formulas for calculation, is proposed. The obtained calculation formulas allow to carry out design and optimization calculations of friction nodes with bearings of slip according to the criterion of durability in wear.